PERBEDAAN SIKLUS MENSTRUASI ANTARA IBU PENGGUNA ALAT KONTRASEPSI IUD DAN KONTRASEPSI SUNTIK DI PUSKESMAS KEMALARAJA - Heriani, Heriani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
This study aimed to determine the differences between the menstrual cycle women using IUDs and Injectable contraceptives at the health center UPTD Kemalaraja. Methodsusing descriptive analytic survey. The population in the study were women using IUDs and Injectable contraceptives at the health center UPTD Kemalaraja December period this sampling 2017. Teknik using accidental sampling with a sample of 60 respondents. Instruments in this study are the use of questionnaires. In women contraceptive IUD users have a normal menstrual cycle is 28-35 days as many as 24 (80%) of the 30 respondents, in women using an injectable contraceptive has short menstrual cycles <28 days, a total of 22 (73.33%) from 30 respondents.There is a difference between mothers who use contraceptive IUD and injecting them is the menstrual cycle, the color of menstrual blood, and long menstrual. Keywords: IUD Contraception,Injectable Contraception, menstrual cycle